New strains of hepatitis B virus genotype E circulating in Nigeria - Oladeinde, Bankole H.; Ekejindu, Ifeoma M.; Omoregie, Richard; Odia, Ikpomwonosa; Aguh, Obiora D.; Okwu, Uchechukwu M. (International Journal of Health Sciences, 2018)
Objective: Hepatitis B virus (HBV) is not uncommon among persons infected with human immunodeficiency virus (HIV). Severity of HBV infection and treatment outcome are associated with specific HBV genotypes. No study has reported the types of HBV genotypes circulating among HIV-infected subjects in Nigeria. This study was designed to determine the prevalence of HBV, as well as its genotypic distribution among HIV-infected subjects in Benin City, Nigeria. Methods: Whole blood was collected from a total of 564 HIV-infected and 250 apparently healthy HIV-negative subjects. Serodiagnosis of HBV infection was done using an immunochromatographic kit. Detection of HBV-DNA and sequencing of amplicons were done using standard molecular techniques. Results: HIV status was not significantly associated with HBV seroinfection (HIV vs. non-HIV: 4.6% vs. 4.0%; odds ratio = 1.168, 95% confidence interval = 0.550, 2.444, and P = 0.854). HIV-infected subjects were observed to have an insignificantly (P = 0.645) higher prevalence of true HBV infection than their non-HIV-infected counterparts (HIV positive vs. HIV negative: 23.1% vs. 10.0%). All patients with true HBV infection were found to harbor HBV genotype E, which did not cluster around other HBV genotype E. Conclusion: This study reports novel strains of HBV genotype E circulating in Nigeria.